Detection of Ball Bearing Damage with Vibration Analysis, Temperature, and Shock Pulse Methods in Accelerated Tests - Apriawan Santoso - Nim: 13113113 , Dwi
Rotation machine is a type machines that is widely used in industry. This machine has many sources of failure, one of the failure is rolling bearing damage. Damage in a rolling bearing will decrease machine performance, so production process will also be disrupted. Therefore, rolling bearing conditions need to be monitored periodically. Rolling bearing damage can be detected by several methods such as vibration analysis, lubricant analysis, temperature measurement, etc. Rolling bearing damage should be detected as early as possible so that the damage elements can be ordered early and the down time becomes shorter. This final project aims to determine the characteristics of ball bearing damage by methods of vibration analysis, temperature and shock pulse in accelerated tests. In these tests, vibration and temperature measurements are measured by online using a NI USB 6009 and the measurement of shock pulses is carried out periodically using the data acquisition Leonova Diamond. Vibration and temperature measurement data are processed by using Matlab, while shock pulse measurement data is processed by using Condmaster Ruby. Based on the tests, it can be concluded the following points: Bearing damageÃ‚Â’s except due to friction is marked by an increase of RMS acceleration vibration value and follows by an increase of temperature. The bearing problems can be indicated by an increase of crest factor and kurtosis values before an increase occurred in the RMS acceleration vibration value. Vibration spectrums show BPFO and FTF frequency components but they do not show for BPFI and BSF frequency components despite damage has occurred to the bearing. Friction that occurs in bearing causes high temperature rise shows in the shape of vibration spectrum. The shock pulse measurement does not provide information concerning accurate bearing condition if the bearing experiences friction.